Turn skill analysis method of a skier's forward/backward motion on kinematics in alpine skiing - Miura, T.; Miura, M. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The purpose of this study is to clarify the skiing skill by analyzing the various body segments motion in response to the forward/backward motion of the CGss of the skier.